Efforts to Increase Motivation and Learning Outcomes through the Google Classroom Application Class V SDN Pulorejo 02 PAI Courses for the Academic Year 2021/2022 - Sumiyati, Sumiyati (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to: 1) describe the PAI online learning process through the application of the google classroom application in class V, 2) find out whether the application of the google classroom application can increase student learning motivation in PAI online learning, 3) find out whether the application of the google classroom application can improve student learning outcomes in PAI online learning material Knowing the Apostles of Allah SWT Class V. This classroom action research uses subjects and research settings for class V in the second semester of the 2021/2022 academic year at SD Negeri Pulorejo 02, Winong District, Pati Regency. The results of observations of the online learning process show that the learning process using the google classroom application has increased the average score from 2.63 in the good category in the first cycle to 3.67 in the very good category in the second cycle. Thus the learning process has increased by 0.97. The results of observations on student learning motivation by learning using the google classroom application showed an average increase from 2.98 in the first cycle to 3.60 in the second cycle or in other words an increase of 0.62 points. Student learning outcomes in the PAI subject matter of Knowing the Apostles of Allah SWT showed an increase, in the initial condition of students who completed the KKM as many as 6 students or 40%, while students who had not completed as many as 9 students or 60% with an average score of 63.60 . It increased in the first cycle, namely among students who completed the KKM by 11 students or 73%, while students who had not completed the KKM were 4 students or 27% with an average score of 77.20. Increasingly in the second cycle, the students who completed the KKM were 14 students or 93%, while the students who had not completed the KKM were only 1 student or 7% with an average score of 91.46. This shows that student learning outcomes have increased significantly